Hubungan Aktivitas Fisik dengan Tekanan Darah pada Mahasiswa Fakultas Kedokteran Universitas HKBP Nommensen Medan di Masa Pandemi COVID-19 - Ompusunggu, Henny Erina Saurmauli; Kadang, Angelitha (Nommensen Journal of Medicine, 2023)
Background: Blood pressure is a very important factor in the body's circulatory system. If there is an increase ordecrease in blood pressure it will affect the balance in the body. High blood pressure, also known as hypertension, affects many people around the world, including in Indonesia itself. One of the factors that affect blood pressure is physical activity.Objective: This study aimed to determine the association between physical activity and blood pressure of students in the Faculty of Medicine, Universitas HKBP Nommensen Medan.Methods: This study was an analytic study with a cross-sectional design. Total respondents was 90 students who were selected using purposive sampling method. This study used primary data, namely a questionnaire to fill in the history of physical activity and direct blood pressure measurements. The association between physical activity and blood pressure was analyzed using the Chi-Square test.Results: In this study, it was found that the majority of respondents were classified as active (74.4%) and had normal blood pressure (74.4%). The results of the Chi-Square test found that there was no association between physical activity and blood pressure in students of the Faculty of Medicine, Universitas HKBP Nommensen Medan (p = 0.240).Conclusion: There is no association between physical activity and blood pressure in students of the Faculty of Medicine, Universitas HKBP Nommensen Medan, during the COVID-19 pandemic.